THE PQRST STRATEGY, READING COMPREHENSION, AND LEARNING STYLES - Miqowati, Alfi Hidayatu; Sulistyo, Gunadi Harry (Indonesian Journal of Applied Linguistics, 2014)
Abstract: This study aims at investigating the effectiveness of the PQRST strategy in students’ reading comprehension, the effectiveness of the PQRST strategy in reading comprehension of students with different learning styles, and the interaction between the PQRST strategy and the students’ learning styles. This study employed a 2x2 factorial design. The subjects were the second semester students of Public Administration Department, Faculty of Political and Social Science, University of Bondowoso. Two classes were randomly selected as the samples of this study. The experimental class was taught by using the PQRST strategy and the non-experimental class by translation and reading aloud. The data were analysed by utilizing non parametric testing: Mann–Whitney U and Kruskall-Wallis. The findings showed that the PQRST strategy statistically impacted students’ reading comprehension compared to the one taught using the translation and reading aloud. But, it was revealed that there was no difference in the reading comprehension of students with different learning styles taught under the PQRST strategy and translation and reading aloud, and there was no interaction between teaching strategies and students’ learning styles. Keywords: PQRST, learning styles, reading comprehension